Ways of republic making : institutional invention in Brazilian republican tradition - Lessa , Renato (2012)
This article suggests an interpretation of the Brazilian republican State and nation building as a process affected by two orders of fictions. The first and fundamental one was formulated, among several Brazilian intellectuals, by Francisco José de Oliveira Vianna in the beginning of the twentieth century. It was based on the assumption that Brazilian social and political history has been marked, since colonial times, by “insolidarism” and by a lack of social and civic bonds among the population. The second order of fictions is a corollary of the first: the lack of social bonds has been compensated for by the presence and the force of public law and constitution making. The article analyzes two crucial moments of (re)invention of the Brazilian Republic – 1932 and 1988 – marked by a clear predominance of constitution and law making. As a result, Brazilian political experience is presented as an everlasting attempt to build a civic and political community against the facts.